FTIR spectroscopy in biomedical research: how to get the most out of its potential. Issue 8 (26th November 2021) - Magalhães, Sandra; Goodfellow, Brian J.; Nunes, Alexandra
Abstract: Fourier Transform Infrared (FTIR) Spectroscopy, in particular ATR-FTIR, is a widely used technique that allows, in a very short time, to screen biological samples and to identify its specific spectral signature, being an important tool for clinical diagnosis and biomarker discovery. FTIR spectroscopy is used to screen cells, tissues and biofluids and is already implemented in biomedicine, mainly in pre-clinical setting. Although the experimental procedure is easy to implement, sample preparation, definition of spectra acquisition parameters and spectral analysis are crucial steps to obtain reliable and reproducible results. However, the selection of experimental conditions for spectral analysis can be a difficult task for researchers because the information is dispersed and often the choice is made in an empirical and inaccurate way. This review gathers and summarizes studies using FTIR in pre-clinical and clinical setting and aims to systematize information and propose some guidelines for FTIR spectroscopy studies of biological samples. This will help new users to prepare samples for FTIR analysis and understand the critical steps to correctly perform spectra pretreatment, preprocessing and statistical analysis and to implement appropriate and evidence-based experimental designs.